Hormigas (Hymenoptera: Formicidae) del estado de Sinaloa, México - Rosas-Mejía, Madaí; Vásquez-Bolaños, Miguel; Gaona García, Griselda; Vanoye-Eligio, Venancio (Instituto de Ecología, A.C., 2020)
Little taxonomic work of ants has been conducted in Mexico, particularly in the north-west states, such as Sinaloa. This study aimed to review the available information for records of ant species in the state of Sinaloa, Mexico. We sampled 11 sites that comprised 61% of the municipalities of Sinaloa and revised articles, web pages and all kinds of available specialized information on Formicidae. A total of 91 species belonging to 35 genera were listed. The reviewed information revealed that 85.7% of ant records involved rural and urban zones, as well as roadsides. Low-deciduous forests accounted for 7.61%, followed by thorn forests and mesquite fields with 2.85 % and 1 %, respectively. A total of eight introduced species for Sinaloa are recognized. This is the first study aimed to document the knowledge of Formicidae in Sinaloa. Further taxonomic research is suggested to explore such diversity and related habitats.